Does chronic corticosteroid therapy affect the concentration of 25(OH)D 3 in the serum of patients with pemphigus? - Marlena Chmielnicka; Anna Woźniacka; Jolanta Dorota Torzecka (Termedia Publishing House, 2014)
Introduction . Pemphigus is an autoimmune blistering disease, characterized by the presence of autoantibodies directed against desmoglein. It is a severe and potentially life-threatening skin disease, requiring prolonged admission of corticosteroids at high doses. This therapy risks the emergence of various side effects. Corticosteroids (CS) impair the absorption of calcium from the digestive tract, increase the urine loss, and inhibit the synthesis of 25(OH)D 3 in the liver and 1,25(OH)D 3 in the kidneys. Proper supply of the body with vitamin D plays a fundamental role in the regulation of calcium and phosphate, the modulation of the immune response, as well as the growth and differentiation of cells. Deficiency of its active metabolites contributes to the development of osteomalacia and osteoporosis, but it can increase the risk of many diseases such as diabetes, metabolic syndrome, and cardiovascular diseases, and also affect the course of an autoimmune disease like pemphigus. Objective. Comparison of the concentrations of 25(OH)D 3 in patients with pemphigus and healthy people as a control group. Material and methods. The study comprised a group of 29 patients with pemphigus (17 women and 12 men) aged between 23 years and 75 years treated from 1994 to 2009 in the Department of Dermatology and Venereology, Medical University of Lodz, as well as 24 healthy volunteers matched appropriately in terms of gender and age. 25(OH)D 3 concentrations were determined by an immunoenzymatic method (Immunodiagnostic AG). Results. In patients with pemphigus the concentration of 25(OH)D 3 was lower than the recommended level (30-80 ng/ml) in 24 (82.8%) persons, including 5 patients (17.2%) who had hypovitaminosis, 9 (31.1%) with deficiency, and 10 (34.5%) with a deficit. In this patient population, the mean 25(OH)D 3 concentration was up to 52.5% lower than in the control group. The demonstrated difference in the distribution of this trait was statistically significant (p < 0.001). Conclusions. Proper supplementation of vitamin D is not only important for long-term treatment with immunosuppressive drugs, but it can also help to reduce the risk of its occurrence in people with certain genetic predispositions.